2016
DOI: 10.1016/j.seizure.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet treatment for pediatric super-refractory status epilepticus

Abstract: Most patients achieved resolution of status epilepticus on KD therapy, suggesting it could be an effective therapy that can be utilized early in the treatment of children with super refractory status epilepticus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
80
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 11 publications
4
80
1
4
Order By: Relevance
“…The rates of KD reported in adults were similar to those reported in pediatric SE. Nine retrospective studies specifically looked at the effectiveness of KD in pediatrics for SE . A total of 85 Patients, 36 (42%) were males, were put on the KD for the treatment of RSE and SRSE, and it was effective in 64 (75%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rates of KD reported in adults were similar to those reported in pediatric SE. Nine retrospective studies specifically looked at the effectiveness of KD in pediatrics for SE . A total of 85 Patients, 36 (42%) were males, were put on the KD for the treatment of RSE and SRSE, and it was effective in 64 (75%).…”
Section: Discussionmentioning
confidence: 99%
“…KD ratio of 4:1 of fats to nonketogenic proteins and carbohydrates was the most commonly reported regimen in adult patients (Tables and ). In contrast, pediatric SE studies have reported other regimens in addition to the 4:1 ratio such as 3:1, 5:1, 6:1, 1:1, 2:1, 2.75:1, 3.2:1, 3.5:1, and 4.5:1. In addition, less restrictive forms of the KD have been used to successfully induce ketone body production, such as the modified Atkins diet (MAD) in Kumada et al and a low‐glycemic index diet (LGIT) in Martikainen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, KD represents an adjunctive therapeutic option for refractory SE in pediatric and adult populations, although the resolution of SE in responsive patients occurs several days after treatment initiation. 17,18 The synergism between MAGL inhibition and KD therefore has clinical significance, representing a potential improvement over the current therapies. In summary, we provide novel evidence showing that MAGL is a promising therapeutic target to achieve a rapid termination of refractory SE and to reduce neuropathologic and neurologic downstream consequences.…”
Section: -38mentioning
confidence: 99%
“…The ketogenic diet was effective in the FIRES case with subsequent weaning off the anesthetic medications and resolution of the refractory status but this continued to have daily seizures after discharge from the hospital despite further treatment with anti-seizure medications. The patient with NORSE did not respond to the diet and died in hospice [18].…”
Section: Discussionmentioning
confidence: 99%